2019
DOI: 10.1101/645986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motility of Enzyme-Powered Vesicles

Abstract: Autonomous nanovehicles powered by energy derived from chemical catalysis have potential applications as active delivery agents. For in vivo applications, it is necessary that the engine and its fuel, as well as the chassis itself, be biocompatible. Enzyme molecules have been shown to generate mechanical force through substrate turnover and are attractive candidates as engines; phospholipid vesicles are biocompatible and can serve as cargo containers.Herein, we describe the autonomous movement of vesicles with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Catalysis-fueled propulsion of biomolecules at the nanoscale is no doubt a fascinating concept and has potential applications in the field of nanoscience and medicine ( 42 49 ). However, mounting experimental and theoretical evidence argue against the mechanism, scale, and even the existence of such phenomenon ( 1 , 2 , 14 , 16 , 38 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Catalysis-fueled propulsion of biomolecules at the nanoscale is no doubt a fascinating concept and has potential applications in the field of nanoscience and medicine ( 42 49 ). However, mounting experimental and theoretical evidence argue against the mechanism, scale, and even the existence of such phenomenon ( 1 , 2 , 14 , 16 , 38 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marangoni flow has also been employed as a propulsion force, e.g., to drive autonomous motion of surfactant-stabilized droplets [16][17][18][19][20] , to induce collective motion 21 , or to navigate in complex environment 22 . Recently, a random surface distribution of enzymes has been shown to propel micromotors in the presence of fuel 4,5 . This inspired us to construct a system, in which asymmetry (i.e., heterogeneous distribution of enzymes) is transient and dynamic, enabled by the inherently fluidic polymer membrane (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the field of nanomotor and micromotor research, the stochastic positioning of propulsive units has been used as an explanation for the observed motility. Specific examples include the stochastic attachment in a fixed position of enzymes to the surface of nanoparticles by Sanchez et al 4 and the conjugation of enzymes to the fluid membrane of liposomes by Sen et al 5 . However, in contrast to nature, stochasticity has never been used in motor systems, or any other synthetic systems, as a purposely introduced component to control the system's features.…”
mentioning
confidence: 99%
“…Extensively, directional motility of the enzyme-powered micro/nanomotors could also be obtained by tuning the external environment or surrounding solute. Sen and co-workers reported a series of vesicles and liposomal protocells coated with different enzymes including catalase, urease, [137] and ATPase, [138,139] and they found that the autonomous movement of these micro/ nanomotors could be regulated by externally imposing a substrate with proper gradient and by adjusting the enzymatic turnover rate. Also different enzymes resulted in distinct positive and negative chemotactic movement, which could be further governed by their interactions with the surrounding solute gradients.…”
Section: Enzyme-powered Micro/nanomotorsmentioning
confidence: 99%